Our violent ends ebook - Gong, Chloe (These Violent Delights, 2021)
An instant #1 New York Times bestseller! Shanghai is under siege in this "tightly paced" ( School Library Journal , starred review) and searingly romantic sequel to These Violent Delights , which New York Times bestselling author Natasha Ngan calls "deliciously dark." The year is 1927, and Shanghai teeters on the edge of revolution. After sacrificing her relationship with Roma to protect him from the blood feud, Juliette has been a girl on a mission. One wrong move, and her cousin will step in to usurp her place as the Scarlet Gang's heir. The only way to save the boy she loves from the wrath of the Scarlets is to have him want her dead for murdering his best friend in cold blood. If Juliette were actually guilty of the crime Roma believes she committed, his rejection might sting less. Roma is still reeling from Marshall's death, and his cousin Benedikt will barely speak to him. Roma knows it's his fault for letting the ruthless Juliette back into his life, and he's determined to set things right—even if that means killing the girl he hates and loves with equal measure. Then a new monstrous danger emerges in the city, and though secrets keep them apart, Juliette must secure Roma's cooperation if they are to end this threat once and for all. Shanghai is already at a boiling point: The Nationalists are marching in, whispers of civil war brew louder every day, and gangster rule faces complete annihilation. Roma and Juliette must put aside their differences to combat monsters and politics, but they aren't prepared for the biggest threat of all: protecting their hearts from each other.